150k views
2 votes
Y+1=5(x-1) in standard form

User Ungeheuer
by
7.5k points

1 Answer

3 votes

To write y+1=5(x-1) in standard form, we need to move all the terms containing variables to the left side of the equation and the constant term to the right side. We can do this by subtracting 5(x-1) from both sides of the equation.

y+1 = 5(x-1)

y+1 - 5(x-1) = 5(x-1) - 5(x-1)

y - 5x + 5 = 0

Now the equation is in standard form:

-5x + y + 5 = 0

We can also write this as:

5x - y = -5

User Jlbang
by
7.7k points